1963
DOI: 10.2307/1293085
|View full text |Cite
|
Sign up to set email alerts
|

Detritus as a Major Component of Ecosystems

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. University of California Press andAmerican Institute of Biological Sciences are collaborating with JSTOR to digitize, preserve and extend access to AIBS Bulletin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1
1

Year Published

1978
1978
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 2 publications
1
42
1
1
Order By: Relevance
“…Several investigations have shown that the nutritive quality of detritus in marine and freshwater environments increases with decreasing size of the detritus particles (Odum & De La Cruz, 1967;Fuss & Smock, 1996;Young & Huryn, 1997), but others have not found such a relationship (Cammen, 1982). In our study, not only the organic matter but the bulk sediment was analyzed.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Several investigations have shown that the nutritive quality of detritus in marine and freshwater environments increases with decreasing size of the detritus particles (Odum & De La Cruz, 1967;Fuss & Smock, 1996;Young & Huryn, 1997), but others have not found such a relationship (Cammen, 1982). In our study, not only the organic matter but the bulk sediment was analyzed.…”
Section: Discussionmentioning
confidence: 83%
“…The different fractions of detritus are also chemically diverse, and their chemical composition is related to the origin of the sediment (Ward et al, 1990;Malcoln & Stanley, 1982). Detritus originating from aquatic macrophytes and phytoplankton, for example, may be an important source of nitrogen and phosphorus for the sediment (Odum & De La Cruz, 1967;Oláh et al, 1987;Tuominem et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study does not intend to suggest that floral resources partitioning among stingless bees and Africanized honeybees could be due to stingless bees' preference for nonfloral resources. Although local human presence probably increased bee occurrence at nonfloral resources, certainly many other nonfloral resources attractive to bees exist in natural habitats (Odum & De la Cruz, 1963;Wiegert & Owen, 1971). Indeed, nonfloral resource dispersion and more rapid transfer in tropical systems can make investigations more difficult, but they should continue in view of the amount and availability of such resources.…”
Section: Fig 2 -Large Number Ofmentioning
confidence: 99%
“…The detritus food chain is one of the major pathways for the nutrient movement in tropical ecosystems (Odum & de la Cruz, 1963;Wiegert & Owen, 1971). Therefore, it must be emphasized that detritus can play a key role in the study of the relationship between bees and nonfloral resources, and can provide valuable insight into the functioning of tropical ecosystems.…”
Section: Introductionmentioning
confidence: 99%